Influência do tipo e densidade do alimento na larvicultura do pacamã Lophiosilurus alexandri Steindachner 1876 (Siluriformes, Pseudopimelodidae) - Coroa, Pedro Gargur dos Santos (2015)
The improvement of technologies is essential to increase the productivity in aquaculture. One of the bottlenecks in the cultive of native species with regard to larval feeding. The pacamã Lophiosilurus alexandri is an endemic species in São Francisco river basin with high potential for aquaculture and nowadays it is showing vulnerable conservation status. The purpose of this study was to evaluate the post-larval performance of L. alexandri from different diets (Artemia sp. and Panagrellus redivivus), concentrations (C300, C500 and C700) and food frequencies (F1, F3 and F6) in experiments lasting ten days. When the food with better performance is evaluated , the Artemia sp. and Artemia sp. with P. redivivus shows higher survival rates as well as higher weight (F = 371.13, p <0.05), length (F = 79.31; p <0.05) and specific growth rate (TCE) (F = 105.97, p <0.01) than post larvae fed only with P. redivivus and post larval without food supply. The second stage used only Artemia sp. as a food due to the better performance. The survival of post larvae stage was not affected by the gradient and the feed frequency, but the weight (F = 46.63, p <0.001), length (p <0.05; F = 38.398) and TCE (F = 36, 91, p <0.05) showed significant differences, in an increasing manner, with the rise of food gradient. From these results, the best performance of L. Alexandri post larvae were obtained from a daily diet feed with higher gradient (C700). The cultivation of L. alexandri should be encouraged in São Francisco basin. Fish stock reduction due to anthropic actions reinforces the importance of repopulation programs in order to try to restore the natural populations and make this species be one of the main important among the species commercially exploited at São Francisco river basin.